2020
DOI: 10.1007/978-3-030-41505-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Aligning IATE Criminal Terminology to SUMO

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…1) Lynx has demonstrated that there is a gap between the public legal information offered by official sources and the legal information provided by commercial systems, and has proved that the gap can be covered fairly cheaply. (Neubert 2009), and criminology (Schmidt et al 2020). 3) Lynx has demonstrated the need to further develop uniform standards across Europe.…”
Section: Impact Of the Projectmentioning
confidence: 99%
“…1) Lynx has demonstrated that there is a gap between the public legal information offered by official sources and the legal information provided by commercial systems, and has proved that the gap can be covered fairly cheaply. (Neubert 2009), and criminology (Schmidt et al 2020). 3) Lynx has demonstrated the need to further develop uniform standards across Europe.…”
Section: Impact Of the Projectmentioning
confidence: 99%